Neutrophils, G‐CSF and their contribution to breast cancer metastasis. (21st September 2017) - Mouchemore, Kellie A.; Anderson, Robin L.; Hamilton, John A.
Abstract : Evidence is mounting for a role for neutrophils in breast cancer progression to metastasis. However, the role of G‐CSF in neutrophil biology in a cancer setting remains to be defined. Herein we discuss the most recent clinical and experimental evidence for neutrophils and G‐CSF in the promotion of metastasis, demonstrating a potential mechanistic link between them. Understanding this link is imperative both for the development of diagnostic tests and for therapies targeting neutrophils to improve the treatment of breast cancer patients with or at risk of developing metastatic disease. As a high neutrophil‐to‐lymphocyte ratio in patients predicts poor outcome, while mild neutropenia predicts an improved outcome, we urge caution in the use of G‐CSF in neutrophil recovery following chemotherapy as there is increasing evidence in preclinical models that G‐CSF can promote metastasis. Abstract : Evidence is mounting for a contribution of neutrophils to breast cancer progression. Herein we discuss recent clinical and experimental evidence that G‐CSF and/or neutrophils promote metastasis. As a high neutrophil‐to‐lymphocyte ratio in patients predicts poor outcome, while mild neutropenia predicts an improved outcome, we urge caution in the use of G‐CSF in neutrophil recovery following chemotherapy.